Introducing comprehensive sexuality education in Italian schools: from the co-construction to the evaluation of a pilot intervention - Alice Chinelli; Marco Ubbiali; Gianluca Paparatto; Eleonora Torri; Angelo Musco; Rosario Galipò; Paolo Meli; Sabrina Bellini; Nicola Catucci; Ludovica Colaprico; Antonella Camposeragna; Massimo Farinella; et al. (BMC, 2024)
Abstract Introduction School-based comprehensive sexuality education (CSE) is a powerful tool that provides young people with information on all aspects of sexuality and is aimed at protecting their sexual and reproductive health and well-being throughout their lives. Currently, CSE is not integrated within the schools' curriculum in Italy. This study describes the co-construction, implementation, and evaluation of a CSE project piloted among students attending lower secondary schools, in four regions of Italy. Evidence-based evaluation will be helpful in promote the inclusion of CSE programs in the Italian schools' curriculum. Methods The pilot scheme was co-constructed by a multidisciplinary curriculum development group through a Delphi process, including educators who conducted the activities. The evaluation followed three directions: the program (based on a literature review of CSE principles and recommended characteristics), implementation (assessing the execution of the program through the analysis of the reflection tools used by the educators), and short-term outcomes (assessing critical thinking and conscious behavioural choices through pre-post and satisfaction surveys). Results The main goal, learning modules and content were defined and structured in five interventions with the students, and two with families and teachers. A total of 638 students were involved in the activity, across 11 schools. Data analysis of pre/post surveys reported a significant increase in knowledge in 12 of the 15 items investigated (p < 0.05), and a high level of satisfaction with the topics addressed. Qualitative analysis added information on the pivotal role of educators in CSE. Conclusions The national piloting of this educational activity provided positive insights regarding the co-construction, implementation and short-outcome evaluation, suggesting potential for scalability and future inclusion of CSE in the curricula of Italian schools.